Pheochromocytoma Is Characterized by Catecholamine-Mediated Myocarditis, Focal and Diffuse Myocardial Fibrosis, and Myocardial Dysfunction - Ferreira, Vanessa M.; Marcelino, Mafalda; Piechnik, Stefan K.; Marini, Claudia; Karamitsos, Theodoros D.; Ntusi, Ntobeko A.B.; Francis, Jane M.; Robson, Matthew D.; Arnold, J. Ranjit; Mihai, Radu; Thomas, Julia D.J.; Herincs, Maria; et al. (Journal of the American College of Cardiology, 2016)
Pheochromocytoma is associated with catecholamine-induced cardiac toxicity, but the extent and nature of cardiac involvement in clinical cohorts is not well-characterized. This study characterized the cardiac phenotype in patients with pheochromocytoma using cardiac magnetic resonance (CMR). A total of 125 subjects were studied, including patients with newly diagnosed pheochromocytoma (n = 29), patients with previously surgically cured pheochromocytoma (n = 31), healthy control subjects (n = 51), and hypertensive control subjects (HTN) (n = 14), using CMR (1.5-T) cine, strain imaging by myocardial tagging, late gadolinium enhancement, and native T1 mapping (Shortened Modified Look-Locker Inversion recovery [ShMOLLI]). Patients who were newly diagnosed with pheochromocytoma, compared with healthy and HTN control subjects, had impaired left ventricular (LV) ejection fraction (<56% in 38% of patients), peak systolic circumferential strain (p < 0.05), and diastolic strain rate (p < 0.05). They had higher myocardial T1 (974 ± 25 ms, as compared with 954 ± 16 ms in healthy and 958 ± 23 ms in HTN subjects; p < 0.05), areas of myocarditis (median 22% LV with T1 >990 ms, as compared with 1% in healthy and 2% in HTN subjects; p < 0.05), and focal fibrosis (59% had nonischemic late gadolinium enhancement, as compared with 14% in HTN subjects). Post-operatively, impaired LV ejection fraction typically normalized, but systolic and diastolic strain impairment persisted. Focal fibrosis (median 5% LV) and T1 abnormalities (median 12% LV) remained, the latter of which may suggest some diffuse fibrosis. Previously cured patients demonstrated abnormal diastolic strain rate (p < 0.001), myocardial T1 (median 12% LV), and small areas of focal fibrosis (median 1% LV). LV mass index was increased in HTN compared with healthy control subjects (p < 0.05), but not in the 2 pheochromocytoma groups. This first systematic CMR study characterizing the cardiac phenotype in pheochromocytoma showed that cardiac involvement was frequent and, for some variables, persisted after curative surgery. These effects surpass those of hypertensive heart disease alone, supporting a direct role of catecholamine toxicity that may produce subtle but long-lasting myocardial alterations.